Metabolic effects of cedar tar on colon cancer cell line of HCT-116: A follow-up study (Annals of Medical Research, 2022)
Aim: Colon cancer is the most common cancer worldwide. Surgery and chemotherapy are widely used in treatment. Recently, the therapeutic properties of natural products, including Cedrus libani, have been investigated for drug development. Cedrus libani extract (cedar tar) has antimicrobial and anticancer properties that can mediate metabolic pathways. Metabolic changes have been identified as the hallmark of cancer, and therefore research has focused on metabolic biology and drugs in basic and clinical studies. This study aims to investigate the effects of cedar tar on the amino acid metabolism in the colon cancer cell line of HCT-116.Materials and Methods: HCT-116 was homogenized in the phosphate buffered saline medium after being incubated with 30 µg/mL of cedar tar for 24 hours. The intracellular free amino acid profile in the samples was analyzed by liquid chromatography-mass spectrometry/mass spectrometry. Statistical data analysis was performed with SPSS V22 and MetaboAnalyst 5.0 programs.Results: We uncovered with cedar tar treatment that apoptotic β-alanine and anserine levels increased, p
Keywords: Amino acid profile; Cedrus libani; Colon cancer; Lc-ms/ms